2012
DOI: 10.1007/s12664-012-0176-2
|View full text |Cite
|
Sign up to set email alerts
|

64-section multiphase CT enterography as a diagnostic tool in the evaluation of obscure gastrointestinal bleeding

Abstract: 64-slice multiphase CT-EG is a useful investigation in the evaluation of both occult and overt OGIB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
3
14
0
1
Order By: Relevance
“…However, the specificity was higher at 71.6%, also similar to previous studies [14,20,21] . The vascular lesions seen in nearly half the patients with positive MPCTE and negative DBE were likely deep in the bowel wall and hence not seen endoscopically.…”
Section: Discussionsupporting
confidence: 91%
“…However, the specificity was higher at 71.6%, also similar to previous studies [14,20,21] . The vascular lesions seen in nearly half the patients with positive MPCTE and negative DBE were likely deep in the bowel wall and hence not seen endoscopically.…”
Section: Discussionsupporting
confidence: 91%
“…20,21 These agents may lead to complications such as disordered electrolyte, nausea, vomiting, diarrhoea, stomach ache and uroschesis. 22,23 In our study, patients were given a laxative regime of magnesium sulphate to clean the intestinal tract, isotonic mannitol to fulfil the bowel filling and avoid disordered electrolyte, anisodamine to prevent peristalsis, and intravenous contrast agent (iopromide, 370 mg I ml 21 ) for contrast-enhanced scanning.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 18 studies, CTE had a pooled yield of 40% compared to 53% for capsule endoscopy [48]. Other studies have shown similar yields for CTE [22,[55][56][57].…”
Section: Diagnostic Techniquesmentioning
confidence: 96%